Performance Of Social Services In The Development Of Homeless And Beggars - Febriani, Febriani; Hastuti, Weni Puji (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This research was conducted at the office of the Department of Social Services in Pekanbaru City. Its aim was to investigate the supervision provided by the Department in handling social welfare issues, including homeless people and beggars in Pekanbaru City. The study sought to identify the factors that hinder the Department's performance in supervising homeless people and beggars in Pekanbaru. Data were collected through observation, interviews, and documentation techniques, and qualitative analysis was used to analyze the data. The research participants included the coordination and rehabilitation staff at the Department of Social Services in Pekanbaru, the task force for social welfare issues (PMKS), homeless people, beggars, and the general public. Purposive sampling was used to select the research sample, and interviews were conducted with homeless people and beggars to obtain optimal results. The results of the research showed that the Department's performance in supervising homeless people and beggars in Pekanbaru was not satisfactory, due to several issues. These include insufficient supervision provided to homeless people and beggars, with many of them still wandering the streets from morning to night. The supervision provided is only given to certain homeless people and beggars, and not all of them have received it. In addition, the Department has limited human resources and facilities for training homeless people and beggars, which has also hindered their performance